1972
DOI: 10.1021/ma60026a016
|View full text |Cite
|
Sign up to set email alerts
|

Helix-Coil Stability Constants for the Naturally Occurring Amino Acids in Water. IV. Alanine Parameters from Random Poly(hydroxypropylglutamine-co-L-alanine)

Abstract: Helix-Coil Stability Constants for Amino Acids in Water 177 Comparison of the Thermal Reaction Rate in Bulk and in Dilute Solution. It is at first sight surprising that the thermal isomerization of side chains of polymers in the rubbery state should proceed as easily as in dilute solution, since changes in the geometry of such bulky groups must require extensive rearrangements in the conformation of neighboring chain molecules. However, the following argument seems to account for the observed behavior. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
74
1

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 0 publications
9
74
1
Order By: Relevance
“…R < 1/2, the transition temperatures between an α-helical state to a non-α-helical state are between T * =0.085 and T * =0.11. These results are qualitatively in good agreement with experiments which show that polyalanine adopts an α-helical conformation in hydrophobic environments such as the solid state or in non-polar organic solutions and a β-structure conformation in polar aqueous solution 88,[106][107][108][109][110][111] . This is similarly observed in experiments on many heterogeneous peptides which can be folded into alternative stable structures by changing the solution conditions such as the pH, salt or organic cosolvent concentration, peptide concentration, and the redox state [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] .…”
Section: Resultssupporting
confidence: 90%
“…R < 1/2, the transition temperatures between an α-helical state to a non-α-helical state are between T * =0.085 and T * =0.11. These results are qualitatively in good agreement with experiments which show that polyalanine adopts an α-helical conformation in hydrophobic environments such as the solid state or in non-polar organic solutions and a β-structure conformation in polar aqueous solution 88,[106][107][108][109][110][111] . This is similarly observed in experiments on many heterogeneous peptides which can be folded into alternative stable structures by changing the solution conditions such as the pH, salt or organic cosolvent concentration, peptide concentration, and the redox state [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] .…”
Section: Resultssupporting
confidence: 90%
“…In spite of the large number of experimental studies conducted in peptides, there is still much debate concerning the propensity of Ala residues to stabilize ␣-helices. Ingwall et al (2) studied runs of Ala n , with n ϭ 10-1,000, flanked by Lys runs, and concluded that short (n ϳ 10) sequences of Ala peptides do not form helices in water (2,3). Similar conclusions were drawn from studies of Ala-rich random sequences.…”
supporting
confidence: 59%
“…Accordingly, polyalanine is expected to adopt an ␣-helical conformation in a nonpolar organic solvent and ␤-structures with coil conformations in a polar aqueous solution. Solid-state (i.e., hydrophobic environment) (42)(43)(44)(45) and aqueous solution (12)(13)(14) measurements of polyalanine support its conformational dependence on the chemical environments with the ubiquity of the ␣-helix and ␤-structures prevailing in hydrophobic and in polar environments, respectively. The dependence of the conformation of alanine on the solvent characteristics (i.e., the polarity and dielectric constant of the solvent) is supported by experimental evidence that the helical propensity of alanine in water shows a dramatic increase on addition of certain alcohols (e.g., trifluoroethanol) (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…However, experimental (12)(13)(14) and computational (4)(5)(6)(15)(16)(17)(18)(19)(20)(21)(22)(23) studies showed that polyalanines tend to adopt random-coil conformations in aqueous solution. The ambiguity of the helical propensities, even for alanine, which is known as an excellent helix former, may indicate that these helical propensity scales do not reflect the intrinsic properties of individual residues irrespective of the environment, and that solvent effects have to be taken into account.…”
mentioning
confidence: 99%
See 1 more Smart Citation